Sir Philip Sidney and the Kingdom of Bohemia: the Correspondence and Friendship of Philip Sidney and Thomas Jordanus von Klausenburg - Dziurová, Šárka (American & British Studies Annual, 2021)
This paper sheds further light on Philip Sidney’s intellectual network in East-Central Europe, particularly in the Kingdom of Bohemia. Sidney (1554–1586) is celebrated as one of the greatest poets of the Elizabethan age. His immense contribution to the development of English literary culture is unquestioned. It is perhaps surprising to learn that he never expressed any great desire to pursue a literary career. His aim was to become a statesman, as his early biographies show. His career as a poet started after 1580, when he was forced to spend time in a country away from court and politics. Sidney’s personal experiences played a hugely important and formative role in his work. He had packed in a great deal into his life by a very young age, graduating from the most prestigious institutions in England and travelling in continental Europe. During his “grand tour,” Sidney established a network of correspondence with some of the leading intellectual figures in Central Europe. This paper will investigate an as-yet-unexplored figure in this network, the epidemiologist Thomas Jordanus von Klausenburg (1539–1585). Jordanus was acquainted with several figures in Sidney’s intellectual circle, including Thaddeus Hagecius ab Hayek (the Czech physician and astronomer), Hubert Languet (the French diplomat and Sidney’s principal mentor while he was in Europe), Johannes Crato (chief physician at the Viennese and Prague court), and Andreas Dudith (the Polish-based Hungarian nobleman, famous for his conversion from Catholic bishop to devout Lutheran).